2020
DOI: 10.1108/edi-04-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Employment discrimination against gender diverse individuals in Western Australia

Abstract: PurposeThis paper explores employment discrimination against gender diverse job applicants and employees in Western Australia (WA).Design/methodology/approachUsing grounded theory, this study draws on semi-structured interviews with respondents (n = 20) who identified as trans women, trans men, nonbinary or agender. Thematic analysis focused on the multiple dimensions of disadvantage experienced by respondents, including subtle, not so subtle and overt types of employment discrimination.FindingsThe authors’ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Individuals have indicated that because of their gender identity or expression, they have been fired, denied a promotion, or not been hired for a job for which they have applied, as well as been verbally harassed, physically attacked, or sexually assaulted at work. Bates et al (2020), who researched employee discrimination of TGD individuals in Western Australia, confirm the claim that TGD employees experience the highest rate of prejudice, stigmatisation and discrimination in the workplace. Previously, Mizock et al (2018) establish that TGD workers experience a lack of proper assistance and limited career promotion prospects, as well as suffer from psychological isolation, which might be through the limitation of customisation of workplace policies.…”
Section: Understanding the Work Experiences Of Transgender And Gender...mentioning
confidence: 67%
“…Individuals have indicated that because of their gender identity or expression, they have been fired, denied a promotion, or not been hired for a job for which they have applied, as well as been verbally harassed, physically attacked, or sexually assaulted at work. Bates et al (2020), who researched employee discrimination of TGD individuals in Western Australia, confirm the claim that TGD employees experience the highest rate of prejudice, stigmatisation and discrimination in the workplace. Previously, Mizock et al (2018) establish that TGD workers experience a lack of proper assistance and limited career promotion prospects, as well as suffer from psychological isolation, which might be through the limitation of customisation of workplace policies.…”
Section: Understanding the Work Experiences Of Transgender And Gender...mentioning
confidence: 67%
“…There have been growing calls to make higher education more gender inclusive (Mckendry and Lawrence, 2020). Moreover, studies have reported employment discrimination against gender diverse individuals as well as studies reporting employment discrimination against gender diverse individuals (Bates et al, 2021;Thuy et al, 2020). We implore future studies to survey larger populations to be more gender inclusive and provide meaningful analyses as well as to conduct qualitative studies that can provide voice to students across all gender categories.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…There have been growing calls to make higher education more gender inclusive (Mckendry and Lawrence, 2020). Moreover, studies have reported employment discrimination against gender diverse individuals as well as studies reporting employment discrimination against gender diverse individuals (Bates et al. , 2021; Thuy et al.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This is consistent with Riseman's (2019) observation that trans and intersex rights and acceptance were somewhat slower than LGB rights to enter the Australian public agenda. Indeed, recent Australian evidence points to the existence of significant barriers to inclusion amongst trans people, in the workplace and otherwise (Bates et al, 2020;Jones, 2016;Sullivan, 2018). In the next section, we describe the data and methods that we deploy to examine trans-inclusive language in the workplace within this institutional context.…”
Section: The Australian Contextmentioning
confidence: 99%